Indoxyl Sulfate Affects Glial Function Increasing Oxidative Stress and Neuroinflammation in Chronic Kidney Disease: Interaction between Astrocytes and Microglia - Adesso, Simona; Magnus, Tim; Cuzzocrea, Salvatore; Campolo, Michela; Rissiek, Björn; Paciello, Orlando; Autore, Giuseppina; Pinto, Aldo; Marzocco, Stefania (Frontiers in Pharmacology, 2017)
Indoxyl sulphate (IS) is a protein-bound uremic toxin that results from the metabolism of dietary tryptophan and accumulates in the blood of patients with impaired renal function, such as chronic kidney disease (CKD). IS is a well known nephrovascular toxin but little is known regarding its effects on cells of the central nervous system (CNS). Considering the growing interest in the field of neurodegenerative complications in CKD, we studied the effect of IS on CNS cells. IS (15-60µM) treatment in C6 astrocyte cells increased reactive oxygen species (ROS) release and decreased nuclear factor (erythroid-derived 2)-like 2 (Nrf2) activation, and heme oxigenase-1 (HO-1) and NAD(P)H dehydrogenase quinone 1 (NQO1) expression. Moreover IS increased Aryl hydrocarbon Receptor (AhR) and Nuclear Factor-kB (NF-kB) activation in these cells. Similiar observations are made in primary mouse astrocytes and mixed glial cells. Inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) expression, tumor necrosis factor (TNF-α) and interleukin 6 (IL-6) release and nitrotyrosine formation were increased by IS (15-60µM) in primary mouse astrocytes and mixed glial cells. IS increased AhR and NF-kB nuclear translocation and reduced Nrf2 translocation and HO-1 expression in primary cells. Moreover neurons incubation with IS (15-60µM) induced cell death in a dose dependent fashion. In vivo data indicate that IS (800 mg/kg, i.p) induced histological changes and an increase in COX-2 expression and in nitrotyrosine formation in mice brain. Taken together, our results show a significant contribution of IS in generating a neurotoxic enviroment and could have a potential role in neurodegeneration. IS could be then considered not only a marker of disease progression but also a potential therapeutical target for CKD-associated neurodegenerative complications.